2009
DOI: 10.1007/s00520-009-0639-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a new, objective prognostic score for terminally ill cancer patients: a multicenter study

Abstract: We developed the new OPS, without clinician's survival estimates but including a new prognostic factor (LDH). This new instrument demonstrated accurate prediction of the 3-week survival. The OPS had acceptable accuracy in this study population (training set). Further validation is required on an independent population (testing set).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
2
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 30 publications
8
60
2
9
Order By: Relevance
“…Therefore, prognostic factors are essential for the survival prediction. Comparable to other studies, we also observed a negative influence of anaemia [37,38,39], leukocytosis [35,40,41,42], low albumin [35,43,44], hypercalcaemia [45], levels of LDH [40,46] and γGT [47,48]. Anorexia and confusion/cognitive impairment also had a negative impact on the survival time of patients, as in other similar studies [49,50,51,52].…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, prognostic factors are essential for the survival prediction. Comparable to other studies, we also observed a negative influence of anaemia [37,38,39], leukocytosis [35,40,41,42], low albumin [35,43,44], hypercalcaemia [45], levels of LDH [40,46] and γGT [47,48]. Anorexia and confusion/cognitive impairment also had a negative impact on the survival time of patients, as in other similar studies [49,50,51,52].…”
Section: Discussionsupporting
confidence: 71%
“…12 The overall accuracy of the 3-week survival was 75.5% when the cutoff score was set at 3.0. 12 Factors included in the OPS were investigated by reviewing the patients' medical records and identified using laboratory data obtained on the day of admission. Laboratory data obtained within 1 week of the day of transfer were used for patients who were initially admitted to other parts of the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the abovementioned representative prognostic models, other prognostic models are proposed, including the indicator of poor prognosis [68], the Vitamin B12/CRP index [69,70], the terminal cancer prognostic score [71], the Chuang prognostic score [72,73], the prognostic 7-day survival formula [74], the Chinese prognostic scale [75], the computerassisted model [76], the Japan palliative oncology study-prognostic index [77], the objective prognostic score [78,79], the prognostic nomogram for terminally ill cancer patients [80], and the symptom-based predictive tool [81]. Further validation studies or comparative studies among those models are warranted.…”
Section: Other Prognosis Prediction Modelsmentioning
confidence: 99%